Project Report on Heat Transfer in Reactangular Duct with Repeated Baffle Blockages - GUDAPATI S R, PUPPALA S K, GUDAPATI G, PREMANAND, MEESALA RAMESH and RAGHURAM L (1992)
INTERNAL GUIDE: MURALIDHAR V S V, MVJCE
Keywords: Heat Transfer